The Impact of Digital Payments on Inflation in G20 Countries - Lie, Clara Faustine; Indraswari, Citra Rahayu (Contemporary Studies in Economic, Finance and Banking, 2025)
A digital payment system is a transaction or payment method that uses digital means without involving cash, offering various benefits, such as transaction effectiveness and efficiency, and promoting financial inclusion. By 2021, 76 percent of adults worldwide will have an account at a bank, other financial institution, or electronic money service provider. Several previous studies have included digital payment system variables, but these were limited to Indonesia and over varying time periods. This study aims to analyze the impact of digital payment systems on inflation in G20 countries, thereby providing an empirical picture of the interaction between technology, monetary policy, and price stability. The study used panel data regression involving digital payment instruments such as debit, credit, and electronic money. The analysis shows that digital payment systems play a significant role in influencing inflation, with varying effects depending on the type of instrument and country characteristics. These findings provide several important implications regarding monetary policy and digital payment system regulations, which must be adapted to the conditions and level of technological development in each country.